A web survey implementation framework : evidence-based design practices - Belfo, Fernando Paulo (2011)
Web surveying is growing in acceptance and use. However, web-based surveys appear to have lower response rates than traditional mail surveys. That may be the result of ineffective strategies for web survey implementation. This work puts together a set of important aspects to be taken into account through several phases of web survey implementation. The resulting framework has been developed to guide researchers in building a successful web survey implementation and is structured in terms of software tool selection, questionnaire design and survey administration phases. Research foundations and delivery concerns are also included in a framework to guide researchers in building an instrument able to increase response rates. Particular attention is given to key design practices under the evidence of their contribution for a successful web surveying implementation.